1994
DOI: 10.1177/095632029400500505
|View full text |Cite
|
Sign up to set email alerts
|

Dipyridamole Potentiates the Activity of Various Acyclic Nucleoside Phosphonates against Varicella-Zoster Virus, Herpes Simplex Virus and Human Cytomegalovirus

Abstract: SummaryDypiridamole (DPM) is widely used in the treatment of cardiovascular diseases as a coronary vasodilator and inhibitor of platelet aggregation. Phosphonylmethoxyethyl (PME) and 3-hydroxy-2-phosphonylmethoxypropyl (HPMP) derivatives of purines and pyrimidines are potent and selective inhibitors of varicella-zoster virus (VZV), herpes simplex virus (HSV) and human cytomegalovirus (HCMV). We have found that DPM markedly potentiates the antiviral effects of the PME derivatives of adenine (PMEA) and 2,S-diami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…Only a slight antiviral effect of DPM in a dose-dependent pattern was noted, and significant cellular toxicity was unlikely. In addition, the 25 M DPM concentration used was similar to that used in other HSV studies, where there was no apparent cellular toxicity with 20 M DPM (14). It does remain possible that DPM is particularly toxic to neurons and that destruction of neurons led to reactivation in ganglia.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…Only a slight antiviral effect of DPM in a dose-dependent pattern was noted, and significant cellular toxicity was unlikely. In addition, the 25 M DPM concentration used was similar to that used in other HSV studies, where there was no apparent cellular toxicity with 20 M DPM (14). It does remain possible that DPM is particularly toxic to neurons and that destruction of neurons led to reactivation in ganglia.…”
mentioning
confidence: 68%
“…DPM has been used occasionally in antiviral studies (18), including investigations of HSV (14). In the latter study, it was not shown to be a potent antiviral.…”
mentioning
confidence: 99%
“…In addition, it would be of interest to investigate the effect of these drugs on wild-type TK ϩ HSV reactivation. While a significant antiviral effect has not been ascribed to these drugs, a synergistic effect with antiviral agents has been reported (37). In addition, while these drugs may not inhibit replication of HSV during lytic infection, inhibition of reactivation, a point of vulnerability when HSV replication is initially very limited, may be sufficient for a clinical effect to be noted.…”
mentioning
confidence: 99%
“…13 Dipyridamole has been found to be able to potentiate the action of acyclic nucleotides in the treatment of herpes viruses, probably through its immunomodulating interferonogenic effect. [14][15][16] Papaverine also has a number of additional immunotropic properties that have not been previously used in pharmacological practice. For example, papaverine has antiviral properties against a broad spectrum of viruses, due to both its direct antiviral effect and its ability to stimulate the production of endogenous interferons.…”
Section: Tuoms P R E S Smentioning
confidence: 99%